Expressão gênica diferencial relacionada ao conteúdo de ferro no músculo em animais nelore - Diniz, Wellison Jarles da Silva (Universidade Federal de São Carlos, 2015)
Iron (Fe) is an essential micronutrient for cellular homeostasis. Structural component of proteins or enzyme cofactor, Fe has participation in important metabolic pathways that include oxidative metabolism, oxygen transport, cell proliferation and immune system function. Despite of its essentiality, Fe has a toxic potential to cells when in excess. So, a sophisticated system is needed to coordinate the process of absorption, recycling, use and storage. Mutations in genes related to homeostasis of this mineral may potentially alter the cellular distribution and storage. Furthermore, the Fe levels affect biological pathways such as carbohydrate and lipid metabolism. Iron content in cattle muscle has been associated with many sensory and technological parameters of meat quality. However, to date, studies that evaluate how the iron levels in the muscle can alter gene expression and the consequences for the metabolism in cattle are still absent. Therefore, this study aims to identify differentially expressed genes, metabolic pathways, gene interactions and potential regulatory biological mechanisms of physiological processes related to meat quality parameters. Longissimus dorsi (LD) muscle were collected at slaughter for total RNA extraction and determination of CFe by optical emission spectrometry (ICP OES). Eight Nelore steers, who are representatives of extreme value for Genetic Genomic Estimate (GEBV) for iron content (CFe), were selected from a reference population of 373 animals. The sequencing of the total mRNA of extreme animals was carried out from the next generation Illumina technology, which resulted in average l9.13 million of reads per sample after quality control and trimming. Data analysis carried out by Tuxedo Suite pipeline identified 49 annotated and differentially expressed genes (DE) (FDR <0.05) between groups of extremes for GEBV value for CFe. From the DE genes, 18 genes were up-regulated and 31 down-regulated for animals of low GEBV for CFe. Candidate genes for meat quality traits were identified in this study and they are related to transport and lipid metabolism. Other pathways identified through functional enrichment analysis include cell growth and development, function of the hematological system, among others. Canonical signaling pathways (interferon signaling, thyroid receptor activation (TR/RXR) and complement system) and canonical metabolic pathways (biosynthesis of stearate, fatty acid biosynthesis and palmitate biosynthesis) were also identified. Although this study did not identify genes with direct role in the regulation of Fe content, our results suggest biological pathways influenced by this mineral and contribute with information to the understanding of their participation in processes affecting quality of meat. This information will be useful in developing strategies that contribute to the production of better quality meat, healthy and nutritionally rich. In addition, this information may help in understanding of metabolic disorders in other species, including humans.
Keywords: Expressão diferencial; Longissimus; Metabolismo de ferro; Transcriptoma; Differential expression; Longissimus; Iron metabolism; Transcriptome; CIENCIAS BIOLOGICAS::GENETICA